Changes in Computer-Analyzed Facial Expressions with Age - Hyunwoong Ko; Kisun Kim; Minju Bae; Myo-Geong Seo; Gieun Nam; Seho Park; Soowon Park; Jungjoon Ihm; Jun-Young Lee (Sensors, 2021)
Facial expressions are well known to change with age, but the quantitative properties of facial aging remain unclear. In the present study, we investigated the differences in the intensity of facial expressions between older (n = 56) and younger adults (n = 113). In laboratory experiments, the posed facial expressions of the participants were obtained based on six basic emotions and neutral facial expression stimuli, and the intensities of their faces were analyzed using a computer vision tool, OpenFace software. Our results showed that the older adults expressed strong expressions for some negative emotions and neutral faces. Furthermore, when making facial expressions, older adults used more face muscles than younger adults across the emotions. These results may help to understand the characteristics of facial expressions in aging and can provide empirical evidence for other fields regarding facial recognition.